Agile Global Software Development: A Systematic Literature Review - Camara, Rafael; Alves, Annelyelthon; Monte, Iury; Marinho, Marcelo L. M. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
Global Software Development (GSD) continues to grow substantially and it is fast becoming the norm and fundamentally different from local Software Engineering development. Withal, agile software development (ASD) has become an appealing choice for companies attempting to improve their performance although its methods were originally designed for small and individual teams. The current literature does not provide a cohesive picture of how the agile practices are taken into account in the distributed nature of software development: how to do it, who, and what works in practice. This study aims to highlight how ASD practices are applied in the context of GSD in order to develop a set of techniques that can be relevant in both research and practice. To answer the research question, "how are agile practices adopted in agile global software development teams?" We conducted a systematic literature review of the ASD and GSD literature. A synthesis of solutions found in seventy-six studies provided 48 distinct practices that organizations can implement, including "collaboration among teams", "agile architecture", "coaching", "system demo" and "test automation". These implementable practices go some way towards providing solutions to manage GSD teams, and thus to embrace agility.